2015
DOI: 10.1099/mic.0.000139
|View full text |Cite
|
Sign up to set email alerts
|

Further characterization of the role of the mitochondrial high-mobility group box protein in the intracellular redox environment of Aspergillus nidulans

Abstract: zé p fasor 52, Hungary HmbB, a predominantly mitochondrial high-mobility group box (HMGB) protein, of Aspergillus nidulans affects diverse biological activities, such as sterigmatocystin production, the maintenance of mitochondrial DNA copy number, germination of asexual and sexual spores, and protection against oxidative stress agents. We hypothesized that the latter correlates with an unbalanced intracellular redox state, in which case, a not yet fully characterized physiological function could be attributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…As the hmbAΔ conidiospores showed a delay germination compard to the hmbA + control, we started the growth tests by inoculating pre-grown, non-sporulating mycelial discs instead of conidiospores as previously described 29 .…”
Section: Methodsmentioning
confidence: 99%
“…As the hmbAΔ conidiospores showed a delay germination compard to the hmbA + control, we started the growth tests by inoculating pre-grown, non-sporulating mycelial discs instead of conidiospores as previously described 29 .…”
Section: Methodsmentioning
confidence: 99%
“…An HmgB deletion strain exhibited a decrease in conidial and ascospore viability, probably due to the importance of HmgB in maintaining mtDNA in spores [ 164 ]. Furthermore, it was also shown that HmgB plays a role in cellular protection against oxidative stress agents, although it is possible that this role is associated with its nuclear functions [ 165 ].…”
Section: Mthmg Proteins Are Rapidly Evolvingmentioning
confidence: 99%
“…This indicates that HmbB may play a role in the structure and function of nuclear chromatin [11]. This hypothesis is further supported by the altered transcription level of numerous nuclear genes in hmbBΔ [11, 16]. Regarding HmbA and HmbC, we have limited knowledge about their function in terms of their physiological roles and transcriptional regulation, however, based on the functions of their yeast homologues, it can be assumed that they modulate the expression of a wide range of genes [10, 14, 17, 18].…”
Section: Introductionmentioning
confidence: 95%
“…Of these three A . nidulans proteins, the physiological role of the dually localized mitochondrial/nuclear HmbB was previously characterized in details [11, 16]. Deletion of hmbB has pleiotropic effects (S1 Table).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation